The compact Oxford-Hachette French dictionary - Corréard, Marie-Hélène; O'Neill, Mary (Oxford University Press, 2013)
The Compact Oxford-Hachette French Dictionary offers over 90,000 words and phrases, and 120,000 translations of contemporary French and English. It covers all the words you need for everday use, carefully selected from evidence from the Oxford Languages Tracker and the Oxford English Corpus. Also includes French cultural and grammar supplements to help you improve your French. -- Provided by publisher